39 Investigation of intermittent palpitations with the micor ECG wristband. (May 2019) - Sarah, Birkhoelzer; Mullan, N; Crombie, J; Archer, P; Gillings, J; Tanner, Mark A
Abstract : Background: Palpitations are a leading cause of referral to cardiology services. The diagnosis of arrhythmia is achieved through establishing a symptom-rhythm correlation. Conventional ambulatory ECG monitoring can fail to capture symptomatic events. Objective: The ECG wristband is a wearable patient-activated lead I ECG recorder (30 seconds per event) permitting long-term monitoring and might offer a useful strategy for the initial investigation of palpitations. Methods: Patients referred to our service for investigation of paroxysmal arrhythmia were considered suitable for use of the MiCor device if they reported palpitations (or arrhythmic symptoms e.g. dizzy spells). Patients with symptoms of syncope or inability to use the device were excluded. Patients were advised to activate the ECG recorder at the time of their symptoms. The ECG recordings were subsequently uploaded to a database and reviewed by a cardiologist. (Figure 1 ) Results: 39 patients (male 14, female 25, ages 13–86 years) were included. 38 patients submitted symptomatic recordings. A symptom-rhythm correlation was achieved in 37/38 (in 1 case no ECG or symptom recording on return of device). Median time to diagnosis was 19 days (1–62). Diagnoses were: sinus rhythm 20 (54%), sinus tachycardia 5 (13%), ventricular ectopics 4 (11%), SVT 6 (16%), atrial fibrillation 2 (5%) with time to diagnosis 16–40 days. Conclusion: The MiCor device achieved a symptom-rhythm correlation in 97%. In the majority of cases this permitted early reassurance and avoided further investigations. Where significant arrhythmia was diagnosed early implementation of therapy (including anticoagulation) was facilitated. The relative ease of use of this ECG recorder make it suitable for use in primary care where it may help reduce delays in diagnosis, improve patient experience, and reduce the number of secondary care referrals (table 1 ). Conflict of Interest: None